2010
DOI: 10.1038/hr.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between exercise and hypertension in spontaneously hypertensive rats: a meta-analysis of experimental studies

Abstract: The effect of exercise on the progression of hypertension and development of heart failure has been extensively studied in spontaneously hypertensive rats (SHRs), but results published thus far have not revealed a clear picture. Studies differ with respect to the age and sex of rats, duration of exercise and exercise protocols. This study was aimed to examine the influence of age at the start of exercise and the effect of the duration of exercise on blood pressure and hypertrophy, which has not been previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 38 publications
4
31
1
4
Order By: Relevance
“…These results agree with those reported by other authors who have evaluated the effects of exercise training in hypertensive humans (40,41,46,47) and animals (2,39). We have also shown that a training-induced MAP fall was strongly associated with both remodeling of skeletal muscle arterioles (normalization of wall-to-lumen ratio) and a reduction of rela-www.bjournal.com.br Braz J Med Biol Res 44(9) 2011 tive hind limb resistance, which were respectively elevated and significantly high in sedentary male SHR compared to age-matched WKY controls (22,25).…”
Section: Effects Of Training On Blood Pressure Levelssupporting
confidence: 82%
See 4 more Smart Citations
“…These results agree with those reported by other authors who have evaluated the effects of exercise training in hypertensive humans (40,41,46,47) and animals (2,39). We have also shown that a training-induced MAP fall was strongly associated with both remodeling of skeletal muscle arterioles (normalization of wall-to-lumen ratio) and a reduction of rela-www.bjournal.com.br Braz J Med Biol Res 44(9) 2011 tive hind limb resistance, which were respectively elevated and significantly high in sedentary male SHR compared to age-matched WKY controls (22,25).…”
Section: Effects Of Training On Blood Pressure Levelssupporting
confidence: 82%
“…These investigators also concluded that the blood pressure-lowering effect was higher when training started during the pre-hypertensive phase or at an early stage, being in this case independent of exercise duration. Considering only young rats in the hypertensive stage, it was also shown that prolonged exercise protocols caused a greater pressure reduction (39). These results confirmed several previous observations by our group regarding the effectiveness of exercise training in reducing blood pressure in males but not in females (22)(23)(24)(25)(26).…”
Section: Effects Of Training On Blood Pressure Levelssupporting
confidence: 81%
See 3 more Smart Citations